Cassava agronomy research and adoption of improved practices in the Philippines: Major achievements during the past 20 years - Evangelio, Fernando A. (International Center for Tropical Agriculture, 2001)
Over the years, research conducted on the crop focused mainly on agronomic, soil fertility maintenance and soil conservation practices. Very few studies were conducted on the basic physiology of the plant. Except for the use of fertilizers and a change in varieties, very few farmers adopted the recommended technology in cassava cultivation. Despite repeated exposure to modern technology, most farmers still follow their own traditional ways of growing the crop. Details of results obtained in the area of cassava agronomy research are presented.